STRATEGI PENGEMBANGAN LAYANAN ANAK DALAM MENINGKATKAN MINAT BACA ANAK DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT DI MASA PANDEMI COVID-19 - Siti Hafifah; Yona Primadesi (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2022)
This study aims to find out what strategies are carried out in children's services to increase children's interest in reading at the Archives and Library Office of West Sumatra Province during the covid-19 pandemic. This research is a qualitative research with a descriptive approach. There are 2 informants in this study, namely primary informants and secondary informants. The main informants in this study were 12 people with details, one child librarian, head of the library development and development section, head of library services, three parents of children, and six children representing kindergarten, elementary and junior high schools. Data collection techniques were carried out by interview, observation, and documentation methods. This study used validation techniques which included extended participation, persistence of observation and triangulation. The results of this study indicate that (1) due to the COVID-19 pandemic, children's interest in reading has decreased in Children's Services at the Archives and Library Office of West Sumatra Province, this is seen based on indicators of children's reading interest, namely; reading frequency level, reading pleasure level, reading encouragement, reading awareness and quantity of reading sources. (2) there needs to be a strategy in developing children's services in increasing children's reading interest, namely by developing human resources or library managers, developing facilities, developing collections, and kids corner services. (3) during the new normal, children's reading interest increases, this can be seen based on indicators of reading interest and existing visitor books.